The Addition of Interdialytic Weight Gain is not Correlated With Intradialytic Hypertension in Chronic Kidney Disease Patients Undergoing Hemodialysis at Roemani Muhammadiyah Hospital Semarang - Nugroho, Elmathiana Delstiene Henyda; Setyoko, Setyoko; Anggraini, Merry Tyas; Dewi, Rachmi; Nugroho, Erlangga Galih Zulva (Poltekkes Kemenkes Aceh, 2024)
Background: Hemodialysis is one of the kidney replacement therapies to overcome nephrology system problems due to decreased glomerular filtration rate. Intradialytic hypertension is still the most common complication in the hemodialysis process, which is 38%. One of the modifiable factors for the occurrence of intradialytic hypertension complications is Interdialytic Weight Gain (IDWG). Intradialytic hypertension can cause new, more complex problems and can even cause death. Purpose: To determine the relationship between the addition of interdialytic weight gain (IDWG) and intradialytic hypertension in chronic kidney disease patients undergoing hemodialysis at Roemani Muhammadiyah Hospital, Semarang. Methods: The type of research used analytical observation with a cross-sectional approach. The subjects in this study were chronic kidney failure patients in the hemodialysis unit of Roemani Muhammadiyah Hospital Semarang who met the inclusion criteria, totaling 51 people. The sampling technique was consecutive sampling and statistically tested using the Fisher Exact test. Results: Based on the results of the comparative test analyzed using Fisher's exact test, a p-value of 1,000 (p > 0.05) was obtained, which means that there is no relationship between Intradialytic Weight Gain (IDWG) and the occurrence of Intradialytic hypertension. Conclusion: There is no relationship between additional interdialytic weight gain and intradialytic hypertension in chronic kidney failure patients undergoing hemodialysis at Roemani Muhammadiyah Hospital, Semarang.